The role of ungulates in nowadays temperate forests. A response to Fløjgaard et al. (DOI:10.1111/gcb.14029). (6th April 2018) - Boulanger, Vincent; Dupouey, Jean‐Luc; Archaux, Frédéric; Badeau, Vincent; Baltzinger, Christophe; Chevalier, Richard; Corcket, Emmanuel; Dumas, Yann; Forgeard, Françoise; Mårell, Anders; Montpied, Pierre; Paillet, Yoan; et al.
Abstract : In Boulanger et al. (2018), we investigated the effects of ungulates on forest plant diversity. By suggesting a revisit of our conclusions regarding ecosystem dynamics since the late Pleistocene, Fløjgaard et al. (2018) came to the conclusion that moderate grazing in forest should be a conservation target. Since major points of our paper were mis‐ or over‐ interpreted, we put the record straight on our study system and on the scope of our conclusions. Finally, we advocate for an assessment of the conservation issues of ungulates in forests not only regarding hypothetical and still debated states of past ecosystems but also considering timely challenges for forest ecosystems.